Compliance with rules and future uncertainty related to the Covid19 pandemic: trust in government, trust in science, and perceived threat. - Riverso, Roberta; Amato, Mario; Verneau, Fabio; La Barbera, Francesco (Psychology Hub, 2022)
During a pandemic, a high level of compliance by citizens with prevention guidelines provided by the Government and scientists is important in order to slow the spread of the virus; nevertheless, there is evidence of people ignoring Government’s and scientists’ recommendation all over the world. In addition, the COVID-19 outbreak, and the mitigating measures as well, have had huge negative effects on citizens’ everyday life, including confinement, separation of families and friends, restriction of movement and personal freedom. These factors, together with the unpredictable duration and likelihood of resurgence of the pandemic, contribute to future uncertainty. The aim of current research is to contribute to the understanding of citizens’ compliance with rules and future uncertainty related to the COVID-19 pandemic. We explored the relations—scarcely investigated so far—of compliance with rules and future uncertainty with three possible antecedents: trust in Government, trust in scientists, and perceived threat. In addition, regarding the last factor, two dimensions have been distinguished, namely perceived seriousness and perceived probability of the threat. Results suggest that compliance is positively associated with trust in Government, whereas future uncertainty is negatively correlated with trust in scientists. Perceived threat correlates with both compliance and uncertainty, and the association with perceived seriousness is larger than with perceived probability.